KESIAPAN IMPLEMENTASI PSAP NOMOR 13 PADA RUMAH SAKIT BLUD PROVINSI SUMATERA SELATAN - Siska Aprianti Kiagus Zainal Arifin Elvi Maryana (JURNAL RISET TERAPAN AKUNTANSI, 2017)
The purpose of this research is to know the Influence of Organizational Commitment, Human Resources Readiness, Infrastructure Facilities and Information Systems on Implementation Readiness of PSAP No. 13 About Representation of Public Service Agency’s Financial Report in South Sumatera Province BLUD Hospital’s. The type of  this  research  is  quantitative  research  using  primary data. Data  collection  was  done by  distributingquestionnaires of 39 copies to staff/employees in the finance department. From the 39 questionnaires distributed,37  exemplars  were  obtained  which  could  be  included  in  the  data  processing.  The  results  showed  that Organizational Commitment, Human Resources Readiness, Infrastructure Facilities and Information System have a positive and significant effect on Readiness Implementation of  PSAP No. 13. Partially, Commitment, HumanResources and Information System have positive and significant effect on Readiness Implementation of  PSAP No.13. However, Infrastructure Facilities does not have influence on Readiness Implementation of PSAP No. 13. The results of this research also shows that the independent variables are able to explain to the readiness of Implementation of PSAP No.13 equal to 83,6%, the rest influenced by other factor not examined in this research.